The testing of a kinetic model of catalytic cracking in the “C-200” Section of the KT -1/1 Installation of oil refining plants in Kazakhstan; Химия и химическая технология в XXI веке - Nazarov G. Y. (Химия и химическая технология на иностранном языке, 2016)
Заглавие с экрана